2013
DOI: 10.3109/02688697.2013.771136
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor invasive phenotypes can predict progression-free survival in glioblastomas

Abstract: It is possible to identify three invasive phenotypes in GBMs using Diffusion tensor imaging , and these three phenotypes have different progression free survival. A minimal phenotype (20% of patients) predicts a greater delay to progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…This measure allows distinction of the tumor core, tumor infiltration, and edema, and a better assessment of tumor extent. Price et al (103) have used this technique to predict the pattern of tumor recurrence, while Mohsen et al (105) recently reported higher survival in patients with a minimally invasive pattern. It can be hypothesized that this finding is correlated with a specific genotype of glioma.…”
Section: Review: Imaging Correlates Of Adult Glioma Genotypesmentioning
confidence: 99%
“…This measure allows distinction of the tumor core, tumor infiltration, and edema, and a better assessment of tumor extent. Price et al (103) have used this technique to predict the pattern of tumor recurrence, while Mohsen et al (105) recently reported higher survival in patients with a minimally invasive pattern. It can be hypothesized that this finding is correlated with a specific genotype of glioma.…”
Section: Review: Imaging Correlates Of Adult Glioma Genotypesmentioning
confidence: 99%
“…Another promising application of DTI imaging is the potential to detect and predict the invasive growth patterns of high-grade tumors such as GBM. 6 A multitude of additional variations of diffusion imaging such as diffusion kurtosis imaging, 7 high b value, 8 histogram curve fitting, 9 functional diffusion maps, 1012 and restriction spectrum imaging 13 are currently under investigation and may provide additional insights into complex tissue environments.…”
Section: Advanced Mri Techniquesmentioning
confidence: 99%
“…To interpret the high-dimensional tensor imaging, a decomposition into isotropic component (p) and anisotropic component (q) was proposed [12]. This method measures the isotropic and anisotropic diffusion of water molecules and has shown its utility in predicting tumor progression [13] and patient survival [14]. More recently, integrating these modalities was considered useful in revealing the intratumoral invasive component [15] and predicting IDH genotype in high-grade gliomas [16].…”
Section: Introductionmentioning
confidence: 99%